Role of spin-orbit coupling in semimetallic bulk Bismuth. (November 2019) - Jena, Soumyasree; Datta, Sanjoy
Abstract: Ever since the prediction of nontrivial topological band structure in Bi1-xSbx and its subsequent experimental verification, semimetallic bismuth (Bi) has been used quite regularly in a large class of topologically nontrivial materials. On top of it, the recent unexpected discovery of superconductivity in the bulk Bismuth has made it an even more enigmatic material. Although, bulk bismuth has been studied quite extensively both theoretically and experimentally, the observation of superconducting ground state in bulk Bismuth at ambient pressure demands elaborate cross-examination of the electronic structure of Bi. Here, we have used density-functional-theory based first principle calculation to probe the system systematically and obtained qualitative agreement with the experimental result. Int erestingly, we have observed the presence of electron pocket close to the symmetry point L and hole pocket near the symmetry point T albeit without the inclusion of spin-orbit coupling. Furthermore, when spin-orbit interaction is taken into account the hole pocket at T disappears and reappears close to Г rather strongly. We demonstrated the importance of structural optimization and proper Brillouin zone sampling in reproducing the semimetallic behaviour of Bi.